2008
DOI: 10.1016/j.febslet.2008.08.025
|View full text |Cite
|
Sign up to set email alerts
|

A conserved dibasic site is essential for correct processing of the peptide hormone AtRALF1 in Arabidopsis thaliana

Abstract: Prohormone proteins in animals and yeast are typically processed at dibasic sites by convertases. Propeptide hormones are also found in plants but little is known about processing. We show for the first time that a dibasic site upstream of a plant peptide hormone, AtRALF1, is essential for processing. Overexpression of preproAtRALF1 causes semidwarfism whereas overexpression of preproAtRALF1(R69A), the propeptide with a mutation in the dibasic site, shows a normal phenotype. RALF1(R69A) plants accumulate only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
35

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 24 publications
5
91
0
35
Order By: Relevance
“…The peptide was cleaved at Met residues by cyanogen bromide, and the resulting mixture was analyzed by MS. Two fragments were identified with molecular masses of 1628 and 1831 Da. The latter corresponds to the middle part of the peptide (residues [9][10][11][12][13][14][15][16][17][18][19][20][21][22] containing the 'inner' Cys 9 -Cys 21 disulfide bond. The former corresponds to the two flanking parts (residues 1-8 and 23-28) held together by the 'outer' Cys 5 -Cys 25 disulfide bond.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide was cleaved at Met residues by cyanogen bromide, and the resulting mixture was analyzed by MS. Two fragments were identified with molecular masses of 1628 and 1831 Da. The latter corresponds to the middle part of the peptide (residues [9][10][11][12][13][14][15][16][17][18][19][20][21][22] containing the 'inner' Cys 9 -Cys 21 disulfide bond. The former corresponds to the two flanking parts (residues 1-8 and 23-28) held together by the 'outer' Cys 5 -Cys 25 disulfide bond.…”
Section: Resultsmentioning
confidence: 99%
“…The loss-of-function gene mutations SDD1 (AtSBT1.2) and ALE1 (AtSBT2.4) lead to abnormal stomatal density and leaf shape, respectively. These results indicate that some subtilases may play a role in developmental processes through the generation of peptide signals (von Groll et al, 2002;Matos et al, 2008). Overexpression of another subtilase (AtSBT5.4) produces a clavata-like phenotype with fasciated inflorescence stems and compounded terminal buds.…”
Section: Introductionmentioning
confidence: 96%
“…[19][20][21] RALF precursors possess a conserved dibasic site upstream to the active peptide, and recent studies have shown that this site is required for pro-peptide processing and activity of both AtRALF1 and AtRALF23. 22,23 In the case of tomato pollen SlRALF, mature peptide was only detected in the medium in an in vitro pollen germination system. 18 These results are also consistent with localization of a Nicotiana benthamiana RALF fused to GFP, which localized first to the ER and later to the cell wall in N. benthamiana leaf cells.…”
Section: Ralf Processing and Localizationmentioning
confidence: 99%
“…Transgenic studies in Arabidopsis showed that overexpression of either AtRALF1 or AtRALF23 resulted in semi-dwarf plants. 22,23 In Medicago trunculata, a root-expressed RALF gene (MtRALFL1) was discovered as being upregulated by nodulation factors. 35 Overexpression of the MtRALFL1 gene in transgenic plants resulted in a reduction in nodules and an increase in aborted infection threads.…”
Section: Possible Mechanisms Of Ralf Actionmentioning
confidence: 99%